(untitled) (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Mihaela Gheorghe analyzes the teaching profession through the archetypal figures of Pygmalion and Sisyphus, drawing parallels between George Bernard Shaw’s Pygmalion and Eugène Ionesco’s The Lesson. Using Henri Bergson’s theory of laughter, the author highlights the professional comic born from vanity and mechanical rigidity. While Shaw’s mentor achieves a transformative—though cynical—success, Ionesco’s professor embodies a destructive, absurd cycle. Ultimately, the study reveals the educator’s perpetual oscillation between creative grandeur and repetitive failure. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.